Are Immigrants Disloyal? The Case of Mexicans in the U.S. - Krystof Kozak (European Journal of American Studies)
This article analyzes the concept of political loyalty in the context of mass migration flows to the U.S. After exploring the evolving notion of political loyalty, it provides a brief historical background of concerns about the political disloyalty of immigrants in the U.S. Based on a review of current literature and surveys, the case of Mexican immigrants as the biggest immigration group is then analyzed in more detail. It is argued that even though immigrants from Mexico are at times accused of potential disloyalty, they can be considered quite loyal, depending on the selected indicators of loyalty used. This paradox is explained by the expansive use of the notion of political loyalty by modern-day U.S. Nativists. The conclusion argues for a more inclusive concept of political loyalty, which would be better suited for the present-day era of large-scale trans-border movements.1. Introduction2. A Definition of Political Loyalty 3. Loyalty Concerns and Immigration in the U.S. Context4. Case Study: Review of loyalty concerns related to immigrants from Mexico 4.1 Allegations of disloyalty4.2 Basic characteristics of immigrants from Mexico4.3 Measuring the loyalty of Mexican immigrants5. Conclusion: Loyalty Concerns and Immigration